ANTIBIOTIC RESISTANCE AMONG CLINICAL ISOLATES OF STAPHYLOCOCCUS AUREUS AND USEFULNESS OF ANTIBIOGRAM - N. KAUR; R. PRASAD; A.VARMA (International Journal of Pharma and Bio Sciences, 2013)
The emerging resistance to antibiotics and the poor pipeline of new antibiotics is creating a major health issue world-wide. The resistance problem demands that a renewed effort be made to seek antibacterial agents effective against pathogenic bacteria resistant to current antibiotics. Cumulative antibiogram is valuable in monitoring the resistance pattern and to improve empirical therapy by increasing knowledge of local outpatient prevalence of antibiotic resistance. In this study, a total of 107 Staphylococcus aureus were isolated from pus, blood, throat swab, urine, tracheal aspirates out of which 84 were identified as methicillin sensitive S. aureus (MSSA) and 23 were methicillin resistant S. aureus (MRSA) by automated identification and susceptibility testing system (Vitek 2 compact) using AST GP-67 card. While testing the in vitro activities of 15 antibiotics against 107 Staphylococcus aureus, of which 76 were collected from inpatients and 31 from outdoor patient department. The analysis is done on the basis of patient location: whether outpatient and inpatient (non-ICU). It is found that the resistance pattern of these isolates (IPD) were penicillin (91.9%) followed by trimethoprim-sulfamethaxzole (85.3%), ciprofloxacin (84.2%), levofloxacin (83.6%), moxifloxacin (60%), erythromycin (46.7%). Less resistance rate was found against tetracycline (13.2%), gentamycin (11.1%), refampicin (2.7%) and clindamycin (1.4%). None of the isolate was resistant to vancomycin, linezolid, nitrofurantoin and quinpreistin/daflopristin.